Impact of risk and lifestyle factors on therapy goals in the treatment of breast cancer and gynecological cancer patients with integrative medicine - Seitz, Katharina; Theuser, Anna Katharin; Antoniadis, Sophia; Beckmann, Matthias; Beierlein, Milena; Brückner, Lena; Au, Katharina; Hack, Carolin (Archives of Gynecology and Obstetrics, 2025)
Background: As a result of advancements in the diagnosis and therapy of cancer, the prognosis for cancer patients has significantly improved. The benefits of a significantly enhanced survival time lead to a more extensive concern with quality of life and managing the side effects during oncological treatment. Implementing integrative medicine strategies has been found to reduce the side effects of therapy and disease. In 2021 the S3 guideline on complementary medicine in oncology was published for the first time, which takes a stand on the most common aspects of complementary and integrative medicine in Germany. The aim was to see whether a previous healthy life style impacts the success of integrative medicine for patients. Methods: Within the framework of a cross-sectional study over 15 months, 120 cancer patients were monitored at a standardized integrative medicine consultancy service at the University Integrative Medicine Center of the University Hospital Erlangen, Department of Gynecology and Obstetrics. The basic questionnaire consisted of questions on socioeconomic background information, lifestyle factors, such as dietary habits or smoking behavior, as well as information on the gynecological situation. Furthermore, an evaluation based on patient-reported therapy goals concerning the reduction of side effects of conventional cancer treatments, enhancement of disease-related quality of life and better stress and disease management, active participation in cancer treatments, mind–body stabilization, and improvements in coping strategies were assessed. In addition, the impact of patient characteristics and lifestyle on the subjective achievement of these outcomes was evaluated to set the answers in context and show its influence. Statistical analysis was performed using SPSS Statistics for Windows version 26 (IBM Corporation, Armonk in New York, USA). Mean, standard deviation, minimum, and maximum were calculated for age and BMI. The other characteristics regarding demographics, lifestyle, tumor disease, and therapy were analyzed based on their respective absolute and relative frequencies. Results: A large majority of the patients' participation goal was to reduce cancer-related side effects (90.8%), second were the aspects of “Improvement of the disease-related quality of life “(72.5%). In both cases, this common goal was only fully achieved for about one quarter of the patients (25.7%/24.1%), but partially achieved in more than half of the asked patients (53.2%/52.9%). Half of the patients reported that they achieved active participation in cancer treatment with integrative medicine. Around 50% partially achieved stabilization of the body, soul, and spirit, stress, disease management, improvement in cancer-related quality of life, and reduced the side effects of conventional cancer therapies. The success of integrative therapy was independent of age, BMI, family status, children, level of education, insurance type, alcohol and tobacco consumption, sport, low-fat diet, daily fruit and vegetable servings, interest in diets, and previous use of diets. Conclusions and discussion: Using a standardized procedure in integrative medicine allows patients to receive high-quality care. The previous standard of living has no effect on the benefits of integrative medicine for the patient. The goals through the use of integrative medicine could be achieved by all patient groups. It is highly encouraged to incorporate counseling and evidence-based integrative medicine into the clinical routines of cancer centers and adapt postgraduate medical education. Finally, the evidence base for the recommendations should also be strengthened by further research into the use of integrative medicine.
CRIS-Team Scopus Importer:2025-04-18
Keywords: Cancer; Complementary and alternative medicine; Gynecological oncology; Integrative medicine; Lifestyle

The Hallmarks of Endometriosis Markenzeichen von Endometriose - Psilopatis, Iason; Burghaus, Stefanie; Au, Katharina; Hofbeck, Louisa; Windischbauer, Lisa-Maria; Lotz, Laura; Beckmann, Matthias (Geburtshilfe und Frauenheilkunde, 2024)
A heuristic tool called the hallmarks of cancer helps to reduce the enormous complexity of cancer phenotypes and genotypes to a preliminary set of guiding principles. Other aspects of cancer have surfaced as possible improvements in our understanding of the disease's mechanisms. Endometriosis is a gynecological disease condition negatively impacting the quality of life of many women. To date, there is no curative treatment for endometriosis. Therapy is aimed at treating the symptoms using hormone therapy, pain therapy and complementary therapy. Chronic pain and overlapping pain syndromes and illnesses can also be treated with multimodal pain therapy and psychosomatic therapy. Endometriosis is, however, a chronic and complex entity which, in this regard, resembles cancer. The present work investigates the hallmarks of endometriosis with a view to summarizing the current research status and paving new ways for future research projects.
CRIS-Team Scopus Importer:2024-06-28
Keywords: endometriosis; epigenetics; genetics; molecular; pathway; signaling

Validation of the Questionnaire for the Structured Assessment of the Use of Complementary Medicine Methods and Procedures in Patients from the S3 Guideline Complementary Medicine in Oncology and Practical Use of it in Patients with Gynecological Cancer Validierung des Fragebogens f r die strukturierte Bewertung der Nutzung komplement rmedizinischer Methoden und Verfahren aus der S3-Leitlinie zur Komplement rmedizin in der Onkologie und praktischer Einsatz bei Patientinnen mit gyn kologischem Krebs - Seitz, Katharina; Theuser, Anna Katharin; Hack, Carolin; Fasching, Peter; Emons, Julius; Brückner, Lena; Au, Katharina; Beckmann, Matthias; Beierlein, Milena (Geburtshilfe und Frauenheilkunde, 2025)
Background For the first time, an S3 guideline on complementary medicine in oncology was published in 2021, 2024 in May version 2.0 was published. The broad spectrum of complementary and integrative medicine was presented at the highest level of evidence, the respective established interventions were comprehensively addressed, and recommendations were made in the case of sufficient data availability. The guideline also contains a questionnaire for a risk-adapted evaluation of utilized CIM (complementary and integrative medicine) interventions. In this article, the clinical validation of this questionnaire from the guideline is carried out, as well as a descriptive analysis of utilization of CIM interventions in a cohort with gynecologial cancer. Methods The present study is a cross-sectional study conducted at the Women's Hospital of the University Hospital Erlangen. In a first stage, rolled out from January to February 2022, fifty patients completed the questionnaire for the structured assessment of the use of complementary medicine from the S3 guideline Complementary Medicine in Oncology, as well as a validation questionnaire. The latter included the comprehensibility of the questions, the time taken to complete them, as well as any problems encountered and suggestions for improvement. After successful validation of the questionnaire, in the second phase, patients with gynecologic cancer were invited to participate in the survey. The patient population was characterized by descriptive analyses of age, educational level, lifestyle factors such as dietary habits and physical activity, as well as tumor characteristics and treatment. In addition, the frequency of complaints and the utilization of complementary interventions and procedures, classified according to their risk of interactions, were analyzed. Results Validation showed that forty-five out of fifty (90%) patients felt that the questionnaire was clear to understand. Forty-seven (94%) of respondents indicated that the time taken to answer the questions was reasonable. In figures, 42% needed less than five minutes and 48% less than ten minutes. When looking at the utilization of CIM in patients with gynecological tumors, most participants were suffering from ovarian cancer (n = 61, 41.8%), followed by endometrial cancer (n = 33, 22.6%), cervical cancer (n = 32, 21.9%) and vulvar cancer (n = 20, 13.7%). In total, the utilization of a CIM intervention was described 267 times. According to the traffic light classification system in the guideline questionnaire the interventions of the green category (low risk for interaction) (n = 124, 46.4%) was the most commonly used. Therapies in the yellow category were used slightly less frequently (n = 93, 34.8%). CIM interventions of the red category were mentioned 50 times (18.7%). Conclusion and Discussion To date, there has been a lack of standardized surveys that explicitly include CIM. The questionnaire published in the S3 guideline is well understandable and concise. It can therefore be used in a structured way not only in research, but also in everyday clinical practice to avoid interactions and increase patients' safety. However, further training of oncologists is required regarding the application of the interventions mentioned in the questionnaire.
CRIS-Team Scopus Importer:2025-12-05
Keywords: cancer; complementary medicine; gynecological oncology; integrative medicine

Verhütungsberatung - zwischen Wunsch und Wirklichkeit die richtige Wahl treffen - Bozzetti, Theresa; Hofbeck, Louisa; Au, Katharina (gynäkologische praxis, 2025)
Choosing the right contraceptive method is an individual and complex decision-making process, influenced by personal needs, medical factors and social developments. In the last decade, the nature of contraception has changed considerably: An increasing desire for hormone-free alternatives and natural contraceptive methods. The contraceptive pill, long the preferred method, is losing popularity in favour of hormone-free alternatives such as the copper intrauterine device (IUD) or barrier methods such as the condom. In addition, natural methods such as cycle tracking are becoming increasingly important. Studies show a growing scepticism towards hormonal contraceptives due to side effects and a more critical social attitude, but at the same time we have seen an increase in the number of abortions in recent years. The COCO study emphasises that patient-centred counselling that takes individual needs into account improves decision-making and places a greater focus on safety. Women rate structured counselling approaches positively, as they facilitate informed choice and increase adherence. The joint decision-making process requires consideration of the patient‘s lifestyle, desire to have children and contraceptive safety requirements. Counselling tailored to the patient, including factors such as additional benefits such as period pain or premenstrual syndrome (PMS), can increase the satisfaction and safety of the chosen method. In the future, individualised counselling approaches should be further strengthened to enable women to make informed decisions.
CRIS-Team Scopus Importer:2025-08-01
Keywords: contraceptive counseling; contraceptives; pill